Laboratory-based surveillance of antimicrobial resistance in regions of Kenya: An assessment of capacities, practices, and barriers by means of multi-facility survey - Moirongo, Rehema Moraa; Aglanu, Leslie Mawuli; Lamshöft, Maike; Adero, Brian Omondi; Yator, Solomon; Anyona, Stephen; May, Jürgen; Lorenz, Eva; Eibach, Daniel (Frontiers in Public Health, 2022)
Background: Adequate laboratory capacity is critical in the implementation of coherent surveillance for antimicrobial resistance (AMR). We describe capacities and deficiencies in laboratory infrastructure and AMR surveillance practices among health facilities in Kenya to support progress towards broader sustainable laboratory-based AMR surveillance. Methods: A convenience sample of health facilities from both public and private sectors across the country were selected. Information was obtained cross-sectionally between 5th October and 8th December 2020 through online surveys of laboratory managers. The assessment covered quality assurance, management and dissemination of AMR data, material and equipment, staffing, microbiology competency, biosafety and certification. A scoring scheme was developed for the evaluation and interpreted as (80% and above) facility is adequate, (60-79%) requires some strengthening and (<60%) needing significant strengthening. Average scores were compared across facilities in public and private sectors, rural and urban settings, as well as national, county and community levels. Results: Among the participating facilities (n=219), the majority (n=135, 61.6%) did not offer bacterial culture testing, 47(21.5%) offered culture services only and 37(16.9%) performed antimicrobial susceptibility testing (AST). The major gaps identified among AST facilities were poor access to laboratory information management technology (LIMT) (score: 45.9%) and low uptake of external quality assessment (EQA) programs for cultures (score 67.7%). Access to laboratory technology was more than two-fold higher in facilities in urban (58.6%) relative to rural (25.0%) areas. Whilst laboratories that lacked culture services were found to have significant infrastructural gaps (average score 59.4%), facilities that performed cultures only (average score: 83.6%) and AST (average score: 82.9%) recorded significantly high scores that were very similar across areas assessed. Lack of equipment was identified as the leading challenge to the implementation of susceptibility testing among 46.8% of laboratories. Conclusions: We identified key gaps in laboratory information management technology, external quality assurance and material and equipment among the surveyed health facilities in Kenya. Our findings suggest that by investing in equipment, facilities performing cultures can be successfully upgraded to provide additional antimicrobial susceptibility testing, presenting a chance for a major leap towards improved AMR diagnostics and surveillance in the country.